Durable high early strength concrete - Porras, Yadira A. (Kansas State University, 2018)
Based on a 2017 report on infrastructure by the American Society of Civil Engineers, 13% of Kansas public roads are in poor condition. Furthermore, reconstruction of a two-lane concrete pavement costs between $0.8 and $1.15 million dollars per lane mile. High early strength Portland cement concrete pavement (PCCP) patches are widely used in pavement preservation in Kansas due to the ability to open to traffic early. However, these repairs done by the Kansas Department of Transportation (KDOT) deteriorate faster than expected, though, prompting a need for inexpensive, durable high early strength concrete repair mixtures that meet KDOT standards (i.e., a 20-year service life). This study developed an experimental matrix consisting of six PCCP patching mixture designs with varying cement content and calcium chloride dosage. The mixtures were subjected to isothermal calorimetry, strength testing, drying shrinkage, and various durability tests. The effects of cement content and calcium chloride dosage on concrete strength and durability were then investigated. In addition, the compressive strength development with time, the split tensile versus compressive strength relationship, and the shrinkage strain of the PCCP patching mixtures were compared to established relationships provided by the American Concrete Institute (ACI). Results showed a maximum 3% increase in total heat generated by various concrete paste samples in isothermal calorimetry testing. The minimum compressive strength of 1,800 psi required by KDOT could likely be obtained using any of the PCCP mixtures, regardless of the cement content or calcium chloride dosage used in the study. Furthermore, surface resistivity tests for mixtures containing calcium chloride could result in erroneous measurements. Only one mixture satisfied the maximum expansion and minimum relative dynamic modulus of elasticity required by KDOT. Some ACI relationships for shrinkage and strength development do not appear to be valid for high early strength PCCP patching mixtures.
Keywords: High early strength; Durability; Rapid repair; Concrete; Pavement; Patches; Calcium chloride; High cement content